Mandated Health Insurance and Provider Reimbursement via Private Insurance - Andrew Friedson; Allison Marier (SAGE Publishing, 2017)
In 2006, Massachusetts passed a reform that required individuals to purchase health insurance and provided subsidized health insurance to low-income individuals. The US Patient Protection and Affordable Care Act (ACA) was modeled after this reform, making Massachusetts an ideal place to look at potential outcomes from the ACA. Postreform, the proportion of the health-insured population in Massachusetts greatly increased, which potentially changed physician reimbursement for procedures as usage of care, particularly preventative care for children increased. We find that reimbursement for well-infant visits rose temporarily by approximately 4% the year after the reform but that the effective price increase did not persist. It is likely that this lack of persistence is due to an increase in the supply of physicians. This has important implications for the ACA, as expanding physician capacity is more difficult on a national level.